نوجوانوں میں بڑھتی ہوئی بے راہ روی کے اسباب اور سیرت طیبہ کی روشنی میں تدارک: ضلع فیصل آباد سے متعلق نوجوانوں سے ایک سروے: Reasons for increasing Delinquency among Youth and its Remedy in the light of Sīra of the Prophet: A Survey of Youth in District Faisalabad (Al-Qamar, 2023)
Islam is a religion of peace which provides excellent rights to the all segments of the society. If these principles of Islam are implemented in true spirit among the individuals, it will construct an ideal society.  Unfortunately, lack of attention in inculcation of Islamic values towards the children brought-up provoke the different problems in the society and when these children attained the age of youth, they incline towards negative activities. This research article highlights the footprint of the Holy Prophet (PBUH) for an ideal society. The research article will also dig out the reasons behind the declining cultural values in the youth.
Keywords: Youth; Indecency; Remedy